1-{3-(4-Chlorophenyl)-5-[4-(propan-2-yl)phenyl]-4,5-dihydro-1H-pyrazol-1-yl}ethanone - B. Narayana (Acta Crystallographica Section E, 2014)
In the title compound, C20H21ClN2O, the dihedral angles between the pyrazole ring (r.m.s. deviation = 0.049 Å) and the benzene and chlorobenzene rings are 84.65 (10) and 3.35 (10)°, respectively. In the crystal, inversion dimers linked by pairs of weak C—H...O interactions generate R22(16) loops. Weak π–π stacking interactions [centroid–centroid distance = 3.8490 (11) Å] are also observed.